Stress, Procrastination, and Government Employees: A Gender based Analysis - Almas Fatima; Imran Ashraf Malik; Shabir Ahmad Bhatti (Social Science Review Archives, 2025)
This study on stress, procrastination, and government employees, with a focus on gender differences, holds significant importance. It can inform employee well-being initiatives, enabling policymakers to develop targeted interventions that promote productivity and job satisfaction. By identifying gender-based differences, organizations can tailor support systems to enhance performance, reduce absenteeism, and increase retention. The study's findings can also contribute to gender-sensitive policies addressing unique needs and challenges of male and female employees. Furthermore, it advances research on occupational stress, providing insights into government employees' experiences and identifying areas for future research. Ultimately, understanding factors influencing employee performance can improve public service delivery, critical for community well-being and development. This study contributes meaningfully to understanding the complex relationships between stress, procrastination, and gender in the workplace, with implications for policy, practice, and research.